Konsep Dasar Prilaku Dan Budaya Organisasi - Ansori Ansori; Hotia Hotia; Juliana Sholehah; Ayu Zahrotul Mila; Remo Andika Putra (Pusat Riset dan Inovasi Nasional, 2024)
Examining the organizational behavior aspect also known as organizational behavior is the goal of this study. The organization is the primary subject of study for organizational behavior, much like it is for other disciplines that focus on organizational dynamics. Members of an organization are governed by the rules and values that make up its culture. One indicator of great organizational performance is a robust organizational culture. Motivation from high performance can boost an organization's efficacy and production.